2013
DOI: 10.1017/s1751731113000694
|View full text |Cite
|
Sign up to set email alerts
|

Chemical markers for rumen methanogens and methanogenesis

Abstract: The targeting of mcrA or 16S rRNA genes by quantitative PCR (qPCR) has become the dominant method for quantifying methanogens in rumen. There are considerable discrepancies between estimates based on different primer sets, and the literature is equivocal about the relationship with methane production. There are a number of problems with qPCR, including low primer specificity, multiple copies of genes and multiple genomes per cell. Accordingly, we have investigated alternative markers for methanogens, on the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 58 publications
2
14
1
Order By: Relevance
“…Several studies (Hook et al, 2011;Lillis et al, 2011) have reported higher numbers of methanogens in rumen solids than in rumen liquid regardless of diet. However, diet may affect the distribution of methanogens between the solid-and liquid-phases of the rumen, with important implications for methanogenesis (McCartney et al, 2013). In the present study, despite not being significant, when compared to control, EO4 increased the proportion of methanogens in the effluents and decreased the proportion of methanogens in residues, suggesting a change in the microbial communities between liquid and solid phases.…”
Section: Discussioncontrasting
confidence: 62%
“…Several studies (Hook et al, 2011;Lillis et al, 2011) have reported higher numbers of methanogens in rumen solids than in rumen liquid regardless of diet. However, diet may affect the distribution of methanogens between the solid-and liquid-phases of the rumen, with important implications for methanogenesis (McCartney et al, 2013). In the present study, despite not being significant, when compared to control, EO4 increased the proportion of methanogens in the effluents and decreased the proportion of methanogens in residues, suggesting a change in the microbial communities between liquid and solid phases.…”
Section: Discussioncontrasting
confidence: 62%
“…Whereas the Mlas and Mlas-mod primers designed by Steinberg and Regan (2009) were primarily developed for clone library construction and qPCR analyses in oligotrophic fen and anaerobic digester sludge, the qmcrA primer set has been widely used to quantify methanogens specifically from the ruminant gastrointestinal tract, which harbors a different methanogen population (Denman et al, 2007). First attempts were made to relate rumen methanogens as quantified by qmcrA primers with whole-animal methane production in small ruminants, but the results show some discrepancies (McCartney et al, 2013). Briefly, Ding et al (2012) reported a highly positive correlation between mcrA DNA abundance and methane yield measured in 12 Tibetan sheep, whereas Morgavi et al (2012) failed to demonstrate a significant relationship for 6 Texel wethers, which could have been due to defaunation applied in the latter study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently biochemical markers using archaeol (2,3-diphytanyl- O -sn-glycerol) also have been developed (McCartney et al, 2013a). In the case of molecular analysis, various methanogen specific primers targeting 16S rRNA gene have been developed (Castro et al, 2004; Yu et al, 2005; Zhou et al, 2011).…”
Section: Methanogenesis and Methanogensmentioning
confidence: 99%